2019
DOI: 10.3390/fi11030076
|View full text |Cite
|
Sign up to set email alerts
|

eHealth Integrity Model Based on Permissioned Blockchain

Abstract: (1) Background: Large eHealth systems should have a mechanism to detect unauthorized changes in patients’ medical documentation, access permissions, and logs. This is due to the fact that modern eHealth systems are connected with many healthcare providers and sites. (2) Methods: Design-science methodology was used to create an integrity-protection service model based on blockchain technology. Based on the problem of transactional transparency, requirements were specified and a model was designed. After that, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…The lack of real-time access in interoperable systems was discussed in 6% (4/70) papers [ 13 , 40 , 70 , 71 ]. The inconsistency of data structures across heterogenous systems makes it difficult to ensure data integrity when data transfer is attempted across interoperable systems; 23% (16/70) papers indicated that blockchain could enhance data integrity across interoperable systems [ 16 - 18 , 33 , 35 - 37 , 40 , 41 , 44 , 49 , 64 , 66 , 72 - 74 ]. Furthermore, data transparency (which refers to the accessibility to data despite its location, data credibility, and data accuracy) across interoperable systems was discussed in 14% (10/70) papers [ 14 , 33 , 40 , 47 , 52 , 59 , 70 , 72 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of real-time access in interoperable systems was discussed in 6% (4/70) papers [ 13 , 40 , 70 , 71 ]. The inconsistency of data structures across heterogenous systems makes it difficult to ensure data integrity when data transfer is attempted across interoperable systems; 23% (16/70) papers indicated that blockchain could enhance data integrity across interoperable systems [ 16 - 18 , 33 , 35 - 37 , 40 , 41 , 44 , 49 , 64 , 66 , 72 - 74 ]. Furthermore, data transparency (which refers to the accessibility to data despite its location, data credibility, and data accuracy) across interoperable systems was discussed in 14% (10/70) papers [ 14 , 33 , 40 , 47 , 52 , 59 , 70 , 72 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The EMR differs from the EHR as it focuses on the internal medical domain of health organizations and is not integrated between health care providers. Blockchain’s use for EHRs, EMRs, and other record systems in which records are originated and controlled by providers was discussed in 51% (36/70) papers [ 11 , 14 - 21 , 27 , 29 , 30 , 33 , 35 - 37 , 40 , 42 - 44 , 46 , 49 , 53 , 55 , 59 , 60 , 63 , 67 , 68 , 72 - 74 , 76 - 78 , 84 ]. Using blockchain to integrate various health record systems (EHR, EMR, PHR, etc), mHealth, and telemedicine platforms can contribute to patient empowerment and patient engagement by providing a synchronized view of patient information to patients and health care providers, to support patient decision making and control.…”
Section: Resultsmentioning
confidence: 99%
“…The inconsistency of data structures across heterogenous systems makes it difficult to ensure data integrity when data transfer is attempted across interoperable systems; 23% (16/70) papers indicated that blockchain could enhance data integrity across interoperable systems [16-18,33,35-37, 40,41,44,49,64,66,72-74]. Furthermore, data transparency (which refers to the accessibility to data despite its location, data credibility, and data accuracy) across interoperable systems was discussed in 14% (10/70) papers [14,33,40,47,52,59,70,72,75,76].…”
Section: How Blockchain Addresses Hit's Challengesmentioning
confidence: 99%
“…RenderXproviders was discussed in 51% (36/70) papers[11,[14][15][16][17][18][19][20][21]27,29,30,33,[35][36][37]40,[42][43][44]46,49,53,55,59,60,63,67,68,[72][73][74][76][77][78]84].…”
mentioning
confidence: 99%
“…Concerning the technical side, the criptography to protect the communications and the storage of medical data is gaining popularity in the eHealth domain. As an example, blockchain technology is a promising solution to face privacy and security concerns [ 26 , 27 , 28 ]. The Internet of Things have the potential to change the physical interaction between the individuals and organizations, aiming at exchanging information in a secure and reliable way through IT infrastructure [ 29 ].…”
Section: Introductionmentioning
confidence: 99%